2022
DOI: 10.3389/fimmu.2022.911778
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Leptospires Limit Dendritic Cell Activation Through Avoidance of TLR4 and TRIF Signaling

Abstract: Leptospira interrogans is a bacterial species responsible for leptospirosis, a neglected worldwide zoonosis. Mice and rats are resistant and can become asymptomatic carriers, whereas humans and some other mammals may develop severe forms of leptospirosis. Uncommon among spirochetes, leptospires contain lipopolysaccharide (LPS) in their outer membrane. LPS is highly immunogenic and forms the basis for a large number of serovars. Vaccination with inactivated leptospires elicits a protective immunity, restricted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
(78 reference statements)
2
3
0
Order By: Relevance
“…Our findings reveal that pathogenic leptospires partially impair MoDC maturation and skew MoDCs-CD4 + T cell interactions toward Treg cells, thereby failing to stimulate CD4 + T cell proliferation. In line with previous work [ 14 ], MoDCs-P exhibited lower expression levels of CD83 and CD80 compared to MoDCs-NP. Although CD86 and HLA-DR did not show significant differences, the overall expression profile of surface markers suggests impaired maturation of MoDCs-P relative to MoDCs-NP.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings reveal that pathogenic leptospires partially impair MoDC maturation and skew MoDCs-CD4 + T cell interactions toward Treg cells, thereby failing to stimulate CD4 + T cell proliferation. In line with previous work [ 14 ], MoDCs-P exhibited lower expression levels of CD83 and CD80 compared to MoDCs-NP. Although CD86 and HLA-DR did not show significant differences, the overall expression profile of surface markers suggests impaired maturation of MoDCs-P relative to MoDCs-NP.…”
Section: Discussionsupporting
confidence: 92%
“…Despite this limitation, we observed higher levels of IL-10 and IL-12p70 secretion in MoDCs-NP compared to MoDCs-P. These findings align with previous studies that have demonstrated greater IL-10 production in MoDCs infected with saprophytic leptospires (serovar Patoc) than those infected with the pathogenic leptospires strain Verdun [14]. Furthermore, MoDCs-NP exhibited higher levels of IL-12p70 production than MoDCs-P, which may potentially indicate an induction toward Th1 cell responses.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, critical antimicrobial responses and the O antigen appear to contribute to this failure [ 40 ]. Another consequence of impaired TLR4–TRIF signaling is reduced CD40 expression in dendritic cells (DC), a vital component for generating memory B cells [ 41 ]. The leptospiral LLS do not seem to have pyrogenic potential and have not been proved cytotoxic [ 31 ].…”
Section: Outer Envelope Toxinsmentioning
confidence: 99%
“…However, TLR4 but not TLR2 plays a critical role in LPS signaling (Takeuchi et al, 1999), and LPS recognition is predominantly mediated by TLR4 (Poltorak et al, 1998). TLR4 belongs to a pattern recognition receptor (PRR), and it mainly expresses in macrophages, dendritic cells, eosinophilic granulocytes, and mastocytes (Cagliero et al, 2022;Jing et al, 2022). LPS can be recognized by TLR4 and activates the signaling pathway related to nuclear factor-kappa B (NF-κB) to promote the expression of cytokine genes and the release of cytokines in immune cells (Khan et al, 2022;Martino et al, 2022).…”
Section: Introductionmentioning
confidence: 99%